2011
DOI: 10.5090/kjtcs.2011.44.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Ascending Aorta and Aortic Arch Replacement under Moderate Hypothermia with Right Brachial and Femoral Artery Perfusion

Abstract: BackgroundSelective antegrade perfusion via axillary artery cannulation along with circulatory arrest under deep hypothermia has became a recent trend for performing surgery on the ascending aorta and aortic arch and when direct aortic cannulation is not feasible. The authors of this study tried using moderate hypothermia with right brachial and femoral artery perfusion to complement the pitfalls of single axillary artery cannulation and deep hypothermia.Materials and MethodsA retrospective analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The combined use of antegrade and retrograde femoral artery perfusion during aortic arch surgery may improve visceral perfusion and minimize retrograde embolization. 12,21,22 We experienced no complications related to IA perfusion, such as pseudoaneurysm or dissection. The relatively long hospital stay was most likely due to the older age of the patients and need for TEVAR for the descending aorta after aortic arch surgery during the same hospitalization (14 patients, 8.9%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The combined use of antegrade and retrograde femoral artery perfusion during aortic arch surgery may improve visceral perfusion and minimize retrograde embolization. 12,21,22 We experienced no complications related to IA perfusion, such as pseudoaneurysm or dissection. The relatively long hospital stay was most likely due to the older age of the patients and need for TEVAR for the descending aorta after aortic arch surgery during the same hospitalization (14 patients, 8.9%).…”
Section: Discussionmentioning
confidence: 87%
“…So, to relieve turbulence of the aortic arch, we use femoral artery perfusion concomitantly and decrease IA perfusion flow. The combined use of antegrade and retrograde femoral artery perfusion during aortic arch surgery may improve visceral perfusion and minimize retrograde embolization …”
Section: Discussionmentioning
confidence: 99%
“…Because the duration of hypothermic circulatory arrest and increasing age are important predictors of temporary neurologic dysfunction and of fine-motor and memory deficits after aortic arch surgery, reducing the duration of circulatory arrest should reduce the prevalence of these complications [ 20 ]. Lastly, while some authorities find it controversial to perform SABP in patients with acute type A dissection due to a higher risk of neurological complications, a number of very recent studies that have shown SABP for acute type A aortic dissection provides acceptable results [ 21 - 24 ].…”
Section: Discussionmentioning
confidence: 99%